2020
DOI: 10.21203/rs.3.rs-61074/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The recombinant subunit vaccine RBD-Fc, consisting of SARS-CoV-2 RBD and human IgG Fc as an immunopotentiator, elicits robust neutralizing antibody responses against SARS-CoV-2 infection

Abstract: The pandemic of COVID-19 caused by SARS-CoV-2 has posed serious threats to global health and economy, thus calling for the development of safe and effective vaccines. The receptor-binding domain (RBD) in the spike protein of SARS-CoV-2 is responsible for its binding to ACE2 receptor. It contains multiple dominant neutralizing epitopes and serves as an important antigen for the development of COVID-19 vaccines. Here, we showed that immunization of mice with a candidate subunit vaccine consisting of SARS-CoV-2 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We and others have shown that RBD-based vaccines are able to induce significantly stronger nAb responses than S protein- or viral particle-based vaccines since RBD contains the main nAb epitopes in S protein ( Chen et al., 2005 ; He et al., 2004 , 2005a , 2005b ; Yang et al., 2020a ). Therefore, RBD-based vaccines are more effective in eliciting pan-β-CoV-B nAbs ( Tai et al., 2020a ) with correspondingly greater potential for development as pan-β-CoV-B vaccines ( Liu et al., 2020b ; Tai et al., 2020b ; Zang et al., 2020 ; Zhu et al., 2020 ) ( Table 1 ). In addition, two new concepts, NII and BNII, can be used to optimize the structure of the RBD by either removing glycan(s) at the conserved region to expose the neutralizing epitopes ( Chen et al., 2014 ) or mask the non-neutralizing epitope(s) in the immunodominant region with glycan(s) ( Du et al., 2016 ) to optimize the structure of the RBD for induction of stronger cross-nAb responses against pan-β-CoV-B viruses.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that RBD-based vaccines are able to induce significantly stronger nAb responses than S protein- or viral particle-based vaccines since RBD contains the main nAb epitopes in S protein ( Chen et al., 2005 ; He et al., 2004 , 2005a , 2005b ; Yang et al., 2020a ). Therefore, RBD-based vaccines are more effective in eliciting pan-β-CoV-B nAbs ( Tai et al., 2020a ) with correspondingly greater potential for development as pan-β-CoV-B vaccines ( Liu et al., 2020b ; Tai et al., 2020b ; Zang et al., 2020 ; Zhu et al., 2020 ) ( Table 1 ). In addition, two new concepts, NII and BNII, can be used to optimize the structure of the RBD by either removing glycan(s) at the conserved region to expose the neutralizing epitopes ( Chen et al., 2014 ) or mask the non-neutralizing epitope(s) in the immunodominant region with glycan(s) ( Du et al., 2016 ) to optimize the structure of the RBD for induction of stronger cross-nAb responses against pan-β-CoV-B viruses.…”
Section: Main Textmentioning
confidence: 99%
“…Our group has demonstrated that immunization of mice with an RBD-Fc subunit vaccine candidate containing SARS-CoV-2 RBD and a human immunoglobulin G (IgG) Fc fragment of human IgG results in the production of high-titer nAb responses against infection by both live and pseudotyped SARS-CoV-2 with NT 50 values of 1:7,166 and 1:10,523, respectively. Notably, IgG purified from the antisera could effectively cross-neutralize infection by SARS-CoV and SARSr-CoV WIV1 strains (Liu et al, 2020b). Zang et al (2020) also used a SARS-CoV-2 RBD-Fc-based subunit vaccine to immunize mice and obtained mouse antisera with strong neutralizing nAb responses against pseudotyped SARS-CoV-2 and SARS-CoV infection with NT 50 values of 1:12,764 and 1:835, respectively.…”
Section: Stem Cell Reportsmentioning
confidence: 99%